2009
DOI: 10.1007/s11270-009-0046-4
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Comet Assay as a Potential Tool in the Assessment of DNA Integrity in Freshwater Zooplankton Affected by Pollutants from Water Treatment Facility

Abstract: In this pilot study, we evaluated the usefulness of the alkaline comet assay as a biomonitoring tool at the level of plankton communities affected by varying water quality. Zooplankton was collected in autumn 2007 and spring 2008 in two shallow lakes, one being predominantly polluted with aluminium compounds as result of water treatment process (Lake Njivice; 45°10′ N, 14°30′ E) and the other unpolluted (Lake Ponikve; 45°05′ N, 14°30′ E) used as control. Water and sediment chemistry parameters were assessed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 60 publications
3
12
0
Order By: Relevance
“…This result was confirmed with Plankton as an Indicator of heavy Metal Pollution in a Freshwater Reservoir [6]. In previous study the Comet assay has been used to investigate the levels of DNA damage in marine and freshwater copepods exposed to different water borne pollutants [6,26]. According to Kumarave et al [27] DNA damage was minimal to moderate (<40%) in Chembarambakkam species and minimal to high (<86%) from species and the results suggested that the Retteri and Velacheri lake are contaminated with different types of genotoxicants.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…This result was confirmed with Plankton as an Indicator of heavy Metal Pollution in a Freshwater Reservoir [6]. In previous study the Comet assay has been used to investigate the levels of DNA damage in marine and freshwater copepods exposed to different water borne pollutants [6,26]. According to Kumarave et al [27] DNA damage was minimal to moderate (<40%) in Chembarambakkam species and minimal to high (<86%) from species and the results suggested that the Retteri and Velacheri lake are contaminated with different types of genotoxicants.…”
Section: Discussionsupporting
confidence: 65%
“…The comet assay study indicated the potential of Cr, when present in excess concentrations induce DNA damage in the cells of copepod organisms. This result was confirmed with Plankton as an Indicator of heavy Metal Pollution in a Freshwater Reservoir [6]. In previous study the Comet assay has been used to investigate the levels of DNA damage in marine and freshwater copepods exposed to different water borne pollutants [6,26].…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations